Nanoengineered Injectable Hydrogels from kappa-Carrageenan and Two-dimensional Nanosilicates for Wound Healing Application - Lokhande, Giriraj (Acta Biomater, 2018)
We report injectable nanoengineered hemostats for enhanced wound healing and tissue regeneration. The nanoengineered system consists of the natural polysaccharide, κ-carrageenan (κCA), loaded with bioactive two-dimensional (2D) nanosilicates. Nanoengineered hydrogels showed shear-thinning characteristics and can be injected for a minimally invasive approach. The hydrogel can be physically crosslinked in presence of monovalent ions and result in mechanically strong hydrogels. By controlling the ratio between κCA and nanosilicates, compressive stiffness of nanoengineered hydrogels can be modulated between 20 to 200kPa. Despite high mechanical stiffness, nanocomposite hydrogels were highly porous with an interconnected network. The addition of nanosilicates to κCA increases protein adsorption on nanocomposite hydrogels that results in enhanced cell adhesion and spreading, platelets binding and reducing the blood clotting time by more than two-fold. Moreover, due to presence of nanosilicates, a range of therapeutic macromolecules could be delivered. The addition of nanosilicates significantly suppressed the release of entrapped vascular endothelial growth factor (VEGF) and facilitated in vitro tissue regeneration and wound healing. Thus, this multifunctional nanocomposite hydrogel could be used as an injectable hemostat and an efficient vehicle for delivery of therapeutics to facilitate tissue regeneration.